Unexpected multiplicity of QRFP receptors in early vertebrate evolution - Larhammar, Dan; Xu, Bo; Bergqvist, Christina A. (Frontiers in Neuroscience, 2014)
The neuropeptide QRFP, also called 26RFa, and its G protein-coupled receptor GPR103 have been identified in all vertebrates investigated. In mammals, this peptide-receptor pair has been found to have several effects including stimulation of appetite. Recently, we reported that a QRFP peptide is present in amphioxus, Branchiostoma floridae, and we also identified a QRFP receptor (QRFPR) that mediates a functional response to sub-nanomolar concentrations of the amphioxus peptide as well as short and long human QRFP (Xu et al., submitted). Because the ancestral vertebrate underwent two tetraploidizations, it might be expected that duplicates of the QRFP gene and its receptor gene may exist. Indeed, we report here the identification of multiple vertebrate QRFPR genes. Three QRFPR genes are present in the coelacanth Latimeria chalumnae, representing an early diverging sarcopterygian lineage. Three QRFP receptor genes are present in the basal actinopterygian fish, the spotted gar. Phylogenetic and chromosomal analyses show that only two of these receptor genes are orthologous between the two species, thus demonstrating a total of four distinct vertebrate genes. Three of the QRFPR genes resulted from the early vertebrate tetraploidizations and were copied along with syntenic neuropeptide Y receptor genes. The fourth QRFPR gene may be an even older and distinct lineage. Because mammals and birds have only a single QRFP receptor gene, this means that three genes have been lost in these lineages, and at least one of these was lost independently in mammals and birds because it is still present in a turtle. In conclusion, these results show that the QRFP system gained considerable complexity in the early stages of vertebrate evolution and still does so in some lineages, and that it has been secondarily reduced in mammals.